(untitled) (Studia theodisca, 2016)
Being an idiot isn’t that bad. Although persons who are called idiots live a life on the margins of society, they possess a special gift of insight and sensitivity, as well as a knowledge of hidden truths and experiences. Strauß revalues the figure of the idiot by approximating it to that of the poet. Both of them use alternative cognitive processes, a vicinity to transcendence and secret lore which is inherent to the solitude they have to bear for their alternative existence. In Lichter des Toren Strauß carries to extremes his thoughts on the figure of the idiot, exposes the roots of the word and introduces a personal poetics of the idiot.